2017
DOI: 10.4269/ajtmh.16-0553
|View full text |Cite
|
Sign up to set email alerts
|

Contextual and Psychosocial Determinants of Effective Handwashing Technique: Recommendations for Interventions from a Case Study in Harare, Zimbabwe

Abstract: Abstract. Handwashing has been shown to considerably reduce diarrhea morbidity and mortality. To decontaminate hands effectively, the use of running water, soap, and various scrubbing steps are recommended. This study aims to identify the behavioral determinants of effective handwashing. Everyday handwashing technique of 434 primary caregivers in high-density suburbs of Harare, Zimbabwe, was observed and measured as an 8-point sum score of effective handwashing technique. Multiple linear and logistic regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…Such commitment should be made in public by caregivers together with their husbands as they have been found to have a major role in the construction of handwashing facilities and dish racks. As reported in other behavior change studies, 36,37,49 public pledges would also help to reach out to more people and, thus, change descriptive norms. Having adequate water at the household increased the confidence of caregivers to wash utensils with soap.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Such commitment should be made in public by caregivers together with their husbands as they have been found to have a major role in the construction of handwashing facilities and dish racks. As reported in other behavior change studies, 36,37,49 public pledges would also help to reach out to more people and, thus, change descriptive norms. Having adequate water at the household increased the confidence of caregivers to wash utensils with soap.…”
Section: Discussionmentioning
confidence: 66%
“…However, it has been successfully used to evaluate water treatment, sanitation, and handwashing behavior. 36,37 The RANAS model is applied in two stages: 1) determine the behavior factors for the individuals under study and 2) select behavior change techniques (BCTs) that should be applied to the identified gaps. 38 Consequently, this can provide scientific guidance on which strategies to follow during an intervention.…”
Section: Introductionmentioning
confidence: 99%
“…The steps asked were as follows: folding sleeves (while it was also possible to declare as not applicable), removing watches and bracelets (while it was also possible to declare as not applicable), removing rings before or during handwashing (while it was also possible to declare as not applicable), using soap, using warm water, soaking hands before using soap (while it was also possible to declare as not applicable if they do not use soap), spreading soap lather throughout the hands (while it was also possible to declare as not applicable if they do not use soap), turning the faucet off with hand, and drying hands with a towel. The question and the steps included are commonly used in a number of studies dealing with handwashing procedure [ 58 , 62 , 63 , 64 ]. For the majority of steps, including them in the applied procedure was interpreted as needed according to the handwashing guidelines [ 7 , 8 , 9 , 52 ], but for the step described as “turning the faucet off with hand”, including it was interpreted as incorrect due to the fact the faucet should not be touched barehanded after handwashing.…”
Section: Methodsmentioning
confidence: 99%
“…Observational studies have reported a positive association between hardware and handwashing practice (Biran et al 2005(Biran et al , 2009Schmidt et al 2009;Friedrich et al 2017). A review by White et al (2020) postulates that providing access to water and soap through a convenient and desirable handwashing facility may be the most effective means to influence behaviour (White et al 2020).…”
Section: Discussionmentioning
confidence: 99%